Scalable synthesis of dodecanethiol-capped bismuth nanoparticles by a solvent-free solid-state grinding method for reduction of 4-nitrophenol to 4-aminophenol - Singh, Dinesh; Poddar, Pankaj (Langmuir, 2023)
Thiol-capped metal nanoparticles have two constituents:an inorganicmetal and an organic molecule as a shell. Both characters are inbuiltin the structure of the metal thiolate. Herein, we have investigatedbismuth dodecanethiolate as a precursor for the synthesis of dodecanethiol-cappedbismuth nanoparticles (Bi NPs) by a solid-state grinding method. Byusing sodium borohydride and bismuth dodecanethiolate, crystallinebismuth nanoparticles are synthesized in a solvent-free environmentat room temperature (24 & PLUSMN; 4 & DEG;C). Bi NPs are tested for catalyticactivity by reducing 4-nitrophenol (4-NP) to 4-aminophenol (4-AP)with an excess of NaBH4. Dodecanethiol-capped bismuth nanoparticlesexhibit an efficient reduction of 4-NP to 4-AP within 12 min. Additionally,these nanoparticles remain catalytically active for up to three cycles.